Amendment of Public Procurement Act 2063 and Regulation 2064: Implications on Development Projects in Nepal - Dahal, Amrit Kumar (Apex Journal of Business and Management, 2024)
This research delves into the significance of public procurement in ensuring fair, competitive, and economical government activities, emphasizing the crucial role of well-structured laws and regulations in this domain. The study particularly focuses on the amendments made to the Public Procurement Act 2063 (PPA 2063) and Public Procurement Regulation 2064 (PPR 2064) in Nepal, exploring their effects on development projects. The subsequent amendments, occurring three times for PPA 2063 and twelve times for PPR 2064 within fifteen years, create an environment of instability, particularly evident in the frequent changes to PPR 2064 within the last four years. The primary factors prompting amendments include Force Majeure, contractors’ and clients’ interests, faulty rules, and political considerations. The global impact of the COVID-19 pandemic further accentuated the need for adjustments in procurement laws to address unforeseen circumstances beyond control. The concerns arise regarding the extension of project completion time and costs due to amendments in PPR 2064, often without clear justifications. Project quality, sustainability, and functionality were unaffected by amendments, but an increase in project safety was noted, coupled with a decrease in construction risks. Disputes among stakeholders escalated due to the frequent and abrupt changes in procurement laws, emphasizing the need for stability and consistency in the regulatory framework.